2018
DOI: 10.1108/apjml-01-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Australian customer willingness to pay and wait for mass-customised products

Abstract: Purpose The purpose of this paper is to find out how consumers constantly trade off the potential extra cost of mass customisation with the additional time they have to wait to receive their customised products. Design/methodology/approach The authors examine this issue by using conjoint analysis to estimate the trade-offs using a sample of Australian consumers. The authors use cluster analysis to form market segments in the three product categories examined. Findings The segments demonstrate that there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…These findings advance previous studies that reported brand attitude, electronic WOM, and customized product design as the predictors of consumers’ WTP a premium price. 97 , 98 Finally, we refer to H9 and H10, which hypothesize that self-determined needs frustration is negatively related to consumer WTP a premium and positively related to vindictive WOM. These results were supported across Pakistan (β=−0.128, p <0.05; β=0.160, p <0.05) and China (β=−0.238, p <0.05; β=0.160, p <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…These findings advance previous studies that reported brand attitude, electronic WOM, and customized product design as the predictors of consumers’ WTP a premium price. 97 , 98 Finally, we refer to H9 and H10, which hypothesize that self-determined needs frustration is negatively related to consumer WTP a premium and positively related to vindictive WOM. These results were supported across Pakistan (β=−0.128, p <0.05; β=0.160, p <0.05) and China (β=−0.238, p <0.05; β=0.160, p <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Marketing is essential in the development of an organisation’s competitive strategies (Storey, 2017). The intent to generate value leads to competitive advantages, along with new challenges, at both the customer and firm levels (Kalantari and Johnson, 2018). The intense competition within service industries has led organisations to adopt transformed economic value originating not only from services/goods but also from that of experiences, particularly over recent decades.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has also been reported that wait times for services adversely affect consumer behavior in hospitals (Mowen et al 1993), supermarkets (Tom and Lucey 1995), airlines (Taylor 1994), and on online shopping (Rajamma et al 2009) and other websites (Nah 2004). Further, some consumers are willing to pay more to decrease wait times (Kalantari and Johnson 2018;Nguyen et al 2019). Therefore, many services exist across various industries that result in additional charges but decrease wait times, such as Amazon's Prime membership, which expedites shipping (Amazon 2019).…”
Section: Two Effects On Purchasing Behaviormentioning
confidence: 99%